Factors associated with liver injury and prognosis in advanced cancer patients treated with immune checkpoint inhibitors. Issue 5 (27th January 2023) - Kaneko, Shun; Asahina, Yasuhiro; Nakagawa, Mina; Murakawa, Miyako; Miyazaki, Yasunari; Asakage, Takahiro; Fukuda, Shohei; Namiki, Takeshi; Kano, Yoshihito; Nagata, Masashi; Tsuchiya, Jun; Miyoshi, Masato; et al.
Abstract: Aim: The use of immune checkpoint inhibitors (ICIs) has increased remarkably, and immune‐related adverse events (irAEs) have also increased. This study aimed to identify factors associated with immune‐related liver injury (irLI), and the relationship between the grades of irLI and overall survival (OS) in patients treated with ICIs. Methods: A total of 571 patients who had been treated for advanced malignancies with ICIs between January 2015 and March 2022 were retrospectively recruited. The presence of liver injury was determined by the aspartate aminotransferase and alanine aminotransferase elevation. The irLI grading was based on Common Terminology Criteria for Adverse Events version 5.0. Results: A total of 50 (8.8%) patients had grade ≥2 irLI and 24 (4.2%) had grade ≥3 irLI. Treatment with anti‐cytotoxic T‐lymphocyte‐associated protein‐4 agents and baseline grade 1 aspartate aminotransferase/alanine aminotransferase elevation were independent predictive factors of grade ≥2 irLI. Treatment with anti‐cytotoxic T‐lymphocyte‐associated protein‐4 was the only independent predictive factor of grade ≥3 irLI. The median OS for patients who experienced any irAEs was significantly longer than of those without irAEs (hazard ratio 0.503, 95% CI 0.398–0.636, p < 0.001). The median OS in patients with grade ≥2 irLI was significantly longer (HR 0.570, 95% CI 0.387–0.838, p = 0.022). There was no significant difference between the median OS in patients with grade ≥3 irLI and the others ( p = 0.11). Conclusion: The incidence of irLI was significantly higher in patients treated with anti‐cytotoxic T‐lymphocyte‐associated protein‐4 agents. Even in patients with pre‐existing grade 1 aspartate aminotransferase/alanine aminotransferase elevation, appropriate follow‐up and control of the irLI can improve the prognosis.